Propagation aspects of vehicle-to-vehicle communications - an overview - Molisch, A.F.; Tufvesson, F.; Karedal, J.; Mecklenbrauker, C. (2009 IEEE Radio and Wireless Symposium, 2009)
Vehicle-to-vehicle (VTV) wireless communications have many envisioned applications in traffic safety, congestion avoidance, etc., but the development of suitable communications systems and standards requires accurate models for the VTV propagation channel. This paper provides an overview of existing VTV channel measurement campaigns, describing the most important environments, and the delay spread and Doppler spreads obtained in them. Statistical as well as geometry-based channel models have been developed based on measurements and intuitive insights. A key characteristic of VTV channels is the nonstationarity of their statistics, which has major impact on the system performance. Extensive references are provided.